SAT0481 DIAGNOSIS AND INITIAL MANAGEMENT OF JUVENILE-ONSET SYSTEMIC LUPUS ERYTHEMATOSUS IN THE UK AND IRELAND. (June 2019) - Lythgoe, Hanna; Pain, Clare; Smith, Eve; Beresford, Michael
Abstract : Background: The incidence of Juvenile-onset Systemic Lupus Erythematosus (JSLE) in the UK is not well described. Furthermore, we do not know how children and young people initially present and when and where they access care. Previous work has described significant variation in time to diagnosis for UK patients 1 . Objectives: To describe how patients with JSLE currently present, are diagnosed and managed across the UK. Methods: Data was collected over 13 months on all children (aged <18 years) in the UK and Ireland with a new diagnosis of JSLE (meeting either American College of Rheumatology classification criteria (ACR-1997) or Systemic Lupus International Collaborating Clinics classification criteria (SLICC-2012)). Data was collected monthly from all UK and Ireland paediatricians using British Paediatric Surveillance Unit (BPSU) methodology 2 and from relevant adult clinicians using a parallel reporting system. Anonymised patient data was collected by the clinician and sent to the study team. Patient consent was not required following Ethical and Confidentiality Advisory Group approval. Results: 102 cases were reported from Sept 2017–Oct 18. 65 cases were excluded (duplicate cases, diagnosis date outside study period, case definition not met, clinical data pending) and 37 included. All patients met SLICC-2012 and 35 patients met ACR-1997. Of the two patients meeting SLICC-2012 but not ACR-1997, one had lupus nephritis on renal biopsy and positive ANA, and the other met the SLICC-2012 hypocomplementaemia criterion. Of the 35 patients meeting ACR-1997, median age at diagnosis was 12.8 years (interquartile range (IQR) 11.8–14.7 years) with female:male gender of 4.8:1 respectively. 24/35 (69%) were non-Caucasian. Median time from symptom onset to diagnosis was 2 months (IQR 1–6 months). The longest delay was 106 months (patient initially diagnosed with Henoch Schnolein Purpura). 9/35 (26%) of patients experienced a delay in diagnosis measured by at least one of: established organ damage due to JSLE at diagnosis (5 patients), review by ≥1 paediatric sub-specialist prior JSLE diagnosis (3 patients) or patient not referred despite medical review (6 patients). The diagnosis was made by or in conjunction with paediatric rheumatology in 21/35 (60%) patients. 4/35 (11%) patients were diagnosed solely by paediatric nephrology, 2/35 (6%) by adult rheumatology, 7/35 (20%) by general paediatrics and 1/35 (3%) by the paediatric infectious diseases team. Of the 12/35 (34%) patients where diagnosis did not involve a rheumatologist 10 were referred to either adult or paediatric rheumatology and 2 patients were managed solely by paediatric nephrology. 31/35 (89%) patients were treated with oral and/or IV steroids and 33/35 (94%) with hydroxychloroquine. Other treatments used were: mycophenolate mofetil (17/35, 49%); rituximab (8/35, 23%); azathioprine (6/35, 17%); methotrexate (5/35, 14%); cyclophosphamide (3/35, 9%); ofatumumab (1/35, 3%); IV immunoglobulin (1/35, 3%); plasmapheresis (1/35, 3%). No patients died within one month of diagnosis. Conclusion: Diagnosis of JSLE involved paediatric rheumatology in 60% of cases. Median time to diagnosis from symptom onset is two months but there is significant variation; future work will focus on factors influencing this. Analysis of final data (2 year incidence data) will facilitate estimation of current UK incidence rate and description of factors affecting time to diagnosis. References: [1] Smith EMD, Foster HE, Gray WK, Taylor-Robinson D and Beresford MW. Predictors of access to care in juvenile systemic lupus erythematosus: evidence from the UK JSLE Cohort Study. Rheumatology2014;53:557-61 [2] RCPCH. British Paediatric Surveillance Unit. http://www.rcpch.ac.uk/bpsu (accessed17th January2019) Disclosure of Interests: None declared